Solar Module Packaging Polymeric Requirements and Selection - Poliskie, Michelle (Taylor & Francis, 2011)
While global demand for photovoltaic (PV) modules has increased approximately 45 percent per year over the past decade, PV modules must be durable and inexpensive to compete with traditional energy resources. Often overlooked as a means to improve solar technology, polymer packaging is not only the key to protecting fragile solar cells from environmental factors, but is also the critical path for increasing the power performance of a PV module Solar Module Packaging: Polymeric Requirements and Selection explores current and future opportunities in PV polymeric packaging, emphasizing how it can simultaneously reduce cost, increase weatherability, and improve a PV module's power. The book offers an insider's perspective on the manufacturing processes and needs of the solar industry and reveals opportunities for future material development and processing. A broad survey of the polymeric packaging of solar cells, the text covers various classifications of polymers, their material properties, and optimal processing conditions. Taking a practical approach to material selection, it emphasizes industrial requirements for material development, such as cost reduction, increased material durability, improved module performance, and ease of processing. Addressing cost and profitability, the author examines the economics behind polymeric packaging and how it influences the selection process used by solar companies. Suitable for nonspecialists in polymer science, the book provides a basic understanding of polymeric concepts, fundamental properties, and processing techniques commonly used in solar module packaging. It presents guidelines for using polymers in commercial PV modules as well as the tests required to establish confidence in the selection process.